Development of A Guided Discovery Learning Model Based on E-Learning in Thematic Learning - Drajat Sukmanto Utomo; Kartono; Widiasih (Postgraduate, University of Mataram, 2023)
The research objectives include several things. The aim is to develop and analyze the effectiveness of an e-learning based guided discovery learning model in thematic learning for class V elementary school. The way to answer the research objectives is to use the ADDIE Research and Development (R&D) model. The school sample for testing the effectiveness of the model developed was selected based on probability sampling. After the sample was determined, the research results showed that the validity of the learning model was very good and could be used, while the results of the effectiveness of the model implementation could be understood through the posttest results and the results of filling out the questionnaire. Based on these results, it can be concluded that classes that use the guided discovery learning model have higher learning outcomes on average. The average learning outcome of students who studied with the e-learning based guided discovery learning model in the test class was 91.47 with a completion rate of 100%, while the control class which used the guided discovery learning model showed an average learning outcome of 88.33.